Animal Feed and Fodders of North-West Himalayan Region - Bhat, T. K. (Indian Farming, 2015)
The IVRI Regional Station at Palampur has the mandate ofinvestigating and solving animal feeds and fodder problem in the North- West Himalayan region. It also carries out detailed diseaseinvestigation and diagnosis work as well. As a mission, the RegionalStation has to achieve optimum and sustainable livestock production using resource-based regional-specific animal husbandry strategies which can go hand-in-hand with the regionals climatic and socioeconomic conditions.